The dilemma of the Malays : rhetorical analysis of selected speeches of Tunku Abdul Rahman Putra, the first Prime Minister Of Malaysia, 1957-1970. - Ahmad, Abd Mua'ti @ Zamri (Pacific and Asian Communication Association, 2011)
This paper discusses a study on the texts of speeches delivered by the former Malaysian Premier Tunku Abdul Rahman Putra Al-Haj throughout his tenure from 1957 to 1970. The analyses were performed in order to see his thought that he uttered every year before his audience especially concerning Malay issues. Each speech text from the total of 26 speeches was examined extensively based on Aristotle’s concept of rhetorical criticisms, emphasizing on the nature of the evidence provided in the arguments and the valid supporting materials used to support such evidence. The Malay issues in the speech texts were analyzed by taking into consideration Aristotle’s rhetorical canons i.e. inventio and dispositio. Briefly, the study found that Tunku’s words concerning Malay issues can be categorized into seven themes, namely the backwardness of the Malays, the Malay language and English, the economic imbalance between the people, education programs for the Malays, Malays and Islam, the discontentment as a source of conflict, and the Malays has no intention to dominate others. Further analysis of his speeches showed Tunku’s firm stand in charting the future of his people, the Malays, to face challenges and to stay competitive. Thus, from the study it can be concluded that in addressing Malay issues, Tunku has made a clear, organized, focused and consistent stand on his subject matter.